Stress analysis of thin and thick plates on elastic foundations using boundary and finite element methods - Al-Hosani, Khaleel Ibrahim Abdulla (Cranfield University, 1991)
In this work an attempt has been made to derive a full finite element and boundary element theory for the analysis of thin and thick plates on elastic foundations. A new high order shear finite element capable of the analysis of thin thick plates has been derived using Hermitian and Lagrangian shape functions. Different new boundary element derivations for the analysis of thin plates on elastic foundations are introduced using 3 degrees-of-freedom per node. A full new derivation of boundary elements for thick plates on elastic foundations using complex Bessel functions is presented. Fourier and Hankel integral transforms have been employed for the derivation of different fundamental solutions required for boundary element analysis. Several techniques for dealing with singular and divergent integrals encountered with boundary integral equations were developed including the use of "Modified Kelvin Functions" and fictitious boundary concept. some case studies with different loading and boundary conditions were tested and proved that the new derivations presented in this work are correct and reliable for the analysis of thin and thick plates on elastic foundations.